A função afim nas avaliações externas e algumas aplicações - Bezerra, Alex José Leão (2023)
Nowadays, there is no way to think about basic education without thinking about external assessments that, every year, take up more space, functioning as a thermometer of the quality of teaching. Therefore, the objective of this work is to show the relevance of the study of affines functions in basic education, initially addressing their definition, the analysis of their graph, the study of their signs, their characterization and some particularities. From there, we will analyze issues of external evaluations in Espírito Santo and national, such as Learning Monitoring Assessment - AMA, Basic Education Assessment Program in Espírito Santo - PAEBES, Diagnostic Assessment (also available by the State Department of Education), Selection process at the Federal Institute of Espírito Santo - IFES, Brazilian Mathematics Olympiad for Public Schools - OBMEP and National High School Exam - ENEM, addressing some common mistakes made by students, presenting a correct solution and discussing some applications.